Economic justice and natural law - Chartier, Gary (Cambridge University, 2013)
Gary Chartier elaborates an account of economic justice rooted in the natural law tradition, explaining how it is relevant to economic issues and developing natural law accounts of property, distribution, and work. He examines a range of case studies related to ownership, production, distribution, and consumption, using natural law theory as a basis for staking positions on a number of contested issues related to economic life and highlighting the potentially progressive and emancipatory dimension of natural law theory.